Behavioural risks in corporate governance : regulatory intervention as a risk management - Okoye, Ngozi Vivian (Routledge research in corporate law., 2015)
Recent cases of corporate failures, including the fixing of LIBOR rates and money laundering issues in the banking industry, highlight how behavioural issues on the part of company directors are significant contributory factors in corporate governance and the success or failure of companies. This book examines how personality and behavioural issues have contributed to major corporate failures, and how this risk may be managed. The book examines behavioural risks in corporate governance, and evaluates the extent to which risk management mechanisms have acknowledged various aspects of behaviour.